2004
DOI: 10.1063/1.1792171
|View full text |Cite
|
Sign up to set email alerts
|

Ordered microstructures by assembly of ABC 3-miktoarm star terpolymers and linear homopolymers

Abstract: Ordered microstructures assembled from the mixture of the ABC 3-miktoarm star terpolymers and the linear homopolymers have been investigated by using dynamic density functional theory. The simulations reveal that completely different ordered microphase pattern is found with addition of a few percent homopolymers that is identical in component to one of the arms on the ABC 3-miktoarm star terpolymer. For example, the original density pattern of ABC 3-miktoarm star terpolymers with parameters of N(A)=N(B)=N(C)=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Apart from experimental characterization, numerical investigations of model chains are the most direct approach to study these systems. Therefore, a lot of effort has been put into the investigation of block copolymer and miktoarm stars based on lattice Monte Carlo algorithms [5][6][7][8][9][10][11][12][13][14][15][16] as well as molecular dynamics, [17][18][19][20][21][22] in many cases focusing the attention to a quantitative description or the graphical presentation of microdomains.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from experimental characterization, numerical investigations of model chains are the most direct approach to study these systems. Therefore, a lot of effort has been put into the investigation of block copolymer and miktoarm stars based on lattice Monte Carlo algorithms [5][6][7][8][9][10][11][12][13][14][15][16] as well as molecular dynamics, [17][18][19][20][21][22] in many cases focusing the attention to a quantitative description or the graphical presentation of microdomains.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that block and graft copolymers with incompatible components exhibit periodic nanophase-separated structures in condensed states due to the strong repulsion forces among the different chemical components. The nanophase-separated structures adopt various morphologies such as spherical, cylindrical, bicontinuous, and lamellar structures in a volume fraction-dependent manner. Attention has been recently focused on experimental and theoretical investigations of ABC star-shaped terpolymers as a result of the attractive nanophase-separated structures that arise from the restricted connectivity among the component chains.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have predicted morphological transition of the ABC star‐shaped terpolymers by computer simulation methods 27–33. Especially Gemma et al have reported on morphological variation of the ABC star‐shaped terpolymers of the type A 1.0 B 1.0 C X , covering wide composition range, 0.17 ≫ X ≫ 25, by the Monte‐Carlo method 28.…”
Section: Introductionmentioning
confidence: 99%